The paper solution : what to shred, what to save, and how to stop it from taking over your life - Woodruff, Lisa K.; Nolan-Pleckham, Mary (G.P. Putnam's Sons, 2020)
"From the "Marie Kondo of paper" comes a simple and accessible guide to paper management"--